P05.18 Comparison of N-acetylaspartate concentration decrease in hippocampal and white brain tissue after whole brain radiotherapy. (19th September 2018) - Pospisil, P; Solar, P; Bulik, M; Burkon, P; Slampa, P; Sana, J; Slaby, O; Jancalek, R; Kazda, T
Abstract: Background: Decreased hippocampal N-acetylaspartate (NAA, marker for viability and density of neurons) concentration after whole brain radiotherapy (WBRT) was described in our previous prospective study utilizing MR spectroscopy (MRS). It may be expected that mature neurons (so-called late-responding tissues in radiobiology) will be relatively radioresistant comparing to the radiosensitive population of hippocampal neuronal stem cells. The MRS spectra obtained from the white matter (WM) unaffected by metastases should therefore be relatively stable or without major variations over time. The aim of this secondary analysis of our previous study is to compare NAA decreases between hippocampus and white matter, which may contribute to elucidation of the mechanism of postradiation impairment of hippocampus leading to changes in cognitive functions after brain radiotherapy. Material and Methods: Patients indicated for WBRT underwent MRS hippocampal examination. The areas of interest were temporal lobes, the voxel layer was modified to contain areas of both hippocampi and a portion of the WM of the occipital lobes. The control examination was performed 4 months after WBRT 10 x 3 Gy. The sum of absolute NAA concentrations in both hippocampi was compared with the sum of NAA absolute concentrations in the occipital lobes WM. Results: In total, 14 patients had available MRS data from hippocampus and WM at both initial and control examinations. The mean decrease in NAA concentration in the hippocampus region was -12.8% (min -1.3%, max -23.9%) and in WM -9.5% (min +12.2%, max -28.7%; Wilcoxon Pair Test, p = 0.33). Conclusion: Study of postradiation changes in the brain, especially the hippocampus and other parts of brain involved in cognitive functioning, contributes to the clarification of the mechanism of alteration after WBRT as an iatrogenic side effect of this treatment in patients with brain metastases. The different response of hippocampus region and WM to irradiation would be in accordance with the hypothesis of a postWBRT alteration of hippocampal radiosensitive stem cells as one the major mechanism of this WBRT toxicity. However, our observed difference (-12.8% versus -9.5%) was not statistically significant, which may be due to the absence of normative standards describing these changes as well as due to a small power in statistical analyses. Further research on postradiotherapy changes in brain is needed to optimize the treatment of patients with brain tumors.